Improving Case Plans and Interventions for Adolescents on Probation: The Implementation of the SAVRY and a Structured Case Planning Form. (January 2019) - Viljoen, Jodi L.; Shaffer, Catherine S.; Muir, Nicole M.; Cochrane, Dana M.; Brodersen, Etta M.
Even when probation officers use risk assessment tools, many of their clients' needs remain unaddressed. As such, we examined whether the implementation of the Structured Assessment of Violence Risk in Youth (SAVRY) and a structured case planning form resulted in better case plans as compared with prior practices (i.e., a nonvalidated local tool and an unstructured plan). Our sample comprised 216 adolescents on probation who were matched via propensity scores. Adolescents in the SAVRY/Structured Plan condition had significantly better case plans than those in the preimplementation condition. Specifically, following implementation, adolescents' high need domains were more likely to be targeted in plans. Plans also scored higher on other quality indicators (e.g., level of detail). These improvements appeared to be due primarily to the structured plan rather than the SAVRY. Overall, our findings highlight that, just as structure can improve risk assessments, so too might structure improve case plans.